A comparative study on the characterization of lignocellulose biomass after using chemical pretreatment methods / Nur Liyana Azmi and Dr. Siti Sabrina Mohd Sukri - Azmi, Nur Liyana; Mohd Sukri, Siti Sabrina (2020)
Agricultural industry is one of major contribution in Malaysia's economy which produce tremendous biomass resourcess, contain any organic matter. This known as a lignocellulose biomass, the most abundantly renewable resourcess on Earth. Lignocellulose biomass is compose a biological polymer namely lignin, hemicellulose and cellulose, which associated with each other by covalent and hydrogen bond. Therefore, the structure of lignocellulose biomass is highly recalcitrance and almost completely unavailable for conversion into commercial products. Thus, the chemical pretreatment which is acid and alkaline pretreatment methods is one of the strategies to desruption of lignocellulose structure. The aim of this study is to determine the effect of characterization and compare the strusture of lignocellulose biomass after chemical pretreatment methods. Sodium hydroxide for alkali pretrreatment and sulfuric acid for acid pretreatment was chose, has the greater effective to enhanced lignocellulose structure. After both pretreatment was done, the physical and chemical structure can be observe. The results of disruption is to enhace the structre by increasing the accessibility of cellulose and also degrade hemicellulose and lignin content. Based on cheractrerization of lignocellulose structure, acid pretreatment is mainly remove hemicellulose succefully while alkali pretreatment is degrade a lignin structure and partia;y remove hemicellulose. Futhremore, the comparison of chemical structure on lignocellulose biomass is observed after done the SEM and FTIR analysis. 4% of sodium hydroxide pretreatmet shown more destruption compare to 4% of sulfuric acid it is because the the degradation of lignin structure lead to hemicellulose removal and enhance the cellulose structure